GREEN BANKING, MANAJEMEN RISIKO, DAN KEPEMILIKAN ASING: ANALISIS DETERMINAN NILAI PASAR PERBANKAN DI INDONESIA - Kusumadewi, Ni Luh Gde Lydia; Paramitadewi, Hyasshinta Dyah Sweztika Lukitaning; Kusumawati, Synthia Madya (Ultimaccounting Jurnal Ilmu Akuntansi, 2025)
Abstract - The aim of this study is to analyze the effect of Green Banking (GB) disclosure and Enterprise Risk Management (ERM) disclosure on the financial performance of banking institutions in Indonesia, with foreign ownership serving as a moderating variable. As environmental concerns intensify, banks face growing pressure to integrate sustainable development principles into their operations and reporting through Green Banking Disclosures. Effective risk disclosure also requires a robust ERM framework to strengthen transparency and investor confidence. Foreign ownership often brings improved governance standards, technological capabilities, and managerial discipline. This study offers a novel perspective by examining the combined influence of sustainability disclosure, risk management practices, and ownership structure on firm performance, an area still underexplored in emerging markets. Hypotheses were tested using linear regression analysis with pooled data processed through SPSS. The results indicate that both Green Banking and ERM disclosures do not have a significant effect on firm performance as measured by Tobin’s Q. In contrast, foreign ownership demonstrates a significant positive impact. As a moderating variable, foreign ownership weakens the relationship between Green Banking Disclosure and firm performance, while the interaction between ERM disclosure and foreign ownership does not show a significant effect. These findings suggest that although disclosure practices are increasingly adopted, they may not yet be perceived by the market as strong value signals, particularly during the heightened uncertainty of the Covid-19 period. This underscores the need for more strategic, credible, and standardized disclosures to enhance market perceptions of sustainability and risk management commitments. Keywords: Green Banking Disclosure; Enterprise Risk Management Disclosure; Firm Performance; Foreign Ownership